2019
DOI: 10.2174/1872213x13666190621125048
|View full text |Cite
|
Sign up to set email alerts
|

Ferulic Acid: A Promising Therapeutic Phytochemical and Recent Patents Advances

Abstract: Background: Among the various phenolics metabolites, ferulic acid is considered as the promising mitigating, restorative and antioxidant agent. Ferulic acid is one of the most commonly found natural products in vegetables, for example, tomatoes, sweet corn, and in rice grain. Phytochemicals are utilized in the treatment of human ailments and these are derived from the dietary compounds. Objective: The present review widely argued the calming restorative capability of ferulic acid alongside the scientific evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(60 citation statements)
references
References 0 publications
0
59
0
1
Order By: Relevance
“…Ferulic acid (FA, 4-hydroxy-3-methoxycinnamic acid), is a naturally occurring phenolic acid with many pharmacological activities. FA has been proven to be effective in many disease models such as depression, diabetes, and Alzheimer's disease [8]. Moreover, FA is widely used in cosmetics due to its melanin blocking and tyrosinase inhibition activities [9].…”
Section: Introductionmentioning
confidence: 99%
“…Ferulic acid (FA, 4-hydroxy-3-methoxycinnamic acid), is a naturally occurring phenolic acid with many pharmacological activities. FA has been proven to be effective in many disease models such as depression, diabetes, and Alzheimer's disease [8]. Moreover, FA is widely used in cosmetics due to its melanin blocking and tyrosinase inhibition activities [9].…”
Section: Introductionmentioning
confidence: 99%
“…Four phenolic acids; p-coumeric acid, sinapic acid, ferulic acid and caffeic acid were found in good amount while quercetin was detected in least quantity. It was reported that the ferulic acid, p-coumeric acid sinapic acid are actively involved in antimicrobial, antiviral, anti-mutagenesis, anti-cancer and diabetes mitigation, anti-inflammatory, anti-neurodegeneration activities, 28,29 Caffeic acid play good role in therapy of Alzheimer’s Brain disease. 30 Other detected phenolics has also been reported for their promising biological activities.…”
Section: Resultsmentioning
confidence: 99%
“…[25] Ferulic acid has the property such as anti-inflammatory, antidiabetic, antiaging, anticancer, and neuroprotective, etc., which relies largely upon their cell antioxidant potential. [26] Meanwhile, SF has the auxiliary ability to decrease the pulmonary pressure, which can improve heart failure, reduce the heart after-load be reduction and kidney congestion combined with the addition of conventional drug therapy. In the present study, the kidney function recovered fastly to the baseline in patients of the SF group.…”
Section: Discussionmentioning
confidence: 99%